2010
DOI: 10.1002/jca.20231
|View full text |Cite
|
Sign up to set email alerts
|

The use of fluid boluses to safely perform extracorporeal photopheresis (ECP) in low‐weight children: A novel procedure

Abstract: Apheresis procedures in small children are technically challenging and require special planning with attention to extracorporeal volume. Discontinuous procedures such as extracorporeal photopheresis (ECP) require additional consideration. Alternative methods to perform ECP have been utilized in small children that require manipulation of mononuclear cells outside the standard closed-loop system. We present a safe and feasible alternative to the procedure for children who weigh less than 40 Kg, while maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Several authors have pointed out that the use of ECP in children presents specific challenges, such as low bodyweight, vascular access, extracorporeal volume, metabolic and haematological problems, and psychological tolerance , Nevertheless, Messina and colleagues were able to treat patients with a bodyweight as low as 10 kg without significant side‐effects . Kanold and colleagues reported the follow‐up of paediatric patients with GVHD, with a particular emphasis on the technical aspects of ECP therapy .…”
Section: Acute Graft‐versus‐host Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have pointed out that the use of ECP in children presents specific challenges, such as low bodyweight, vascular access, extracorporeal volume, metabolic and haematological problems, and psychological tolerance , Nevertheless, Messina and colleagues were able to treat patients with a bodyweight as low as 10 kg without significant side‐effects . Kanold and colleagues reported the follow‐up of paediatric patients with GVHD, with a particular emphasis on the technical aspects of ECP therapy .…”
Section: Acute Graft‐versus‐host Diseasementioning
confidence: 99%
“…The challenge of treating low‐bodyweight paediatric patients (as low as 15 kg) was also addressed in a study of patients with both aGVHD and cGVHD . In contrast to many groups that have used an ‘offline’, two‐stage technique for mononuclear cell collection and irradiation, this group reported the use of a sterile, closed‐loop procedure, in which patients received fluid boluses of normal saline or 5% albumin to boost blood volume before, and if needed during, ECP procedures.…”
Section: Acute Graft‐versus‐host Diseasementioning
confidence: 99%
“…These were treated with normal saline flushes or TPA and required CVL change on two occasions. 59 Steroid sparing should be an important goal of secondline therapy, a feature that has not been consistently examined across ECP studies. One important consideration when using ECP especially for SR-cGVHD is the time needed to achieve an objective response.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to counteract the challenge of treating pediatric patients with low bodyweight (as low as 15 kg) for both aGVHD and cGVHD, Schneiderman et al 59 reported the use of a sterile, closed-loop procedure, where patients received fluid boluses of normal saline or 5% albumin to boost blood volume before and, if needed, during ECP procedures. The process was well tolerated by patients and therefore could extend the use of continuous-flow ECP to these patients with low body weight.…”
mentioning
confidence: 99%
“…Conventional extracorporeal photopheresis (ECP) performed using apheresis devices has proven efficient for the treatment of acute and chronic graft‐vs‐host‐disease (GVHD) . The experimental modifications of the conventional ECP procedure have been developed, involving ECP‐treated allogeneic cells, ECP treated enriched or depleted cell populations, mini‐ECP, and cryopreservation of ECP‐treated cells .…”
Section: Introductionmentioning
confidence: 99%